2013
DOI: 10.1371/journal.ppat.1003636
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Enhancer Looping and Differential Gene Targeting by Epstein-Barr Virus Transcription Factors Directs Cellular Reprogramming

Abstract: Epstein-Barr virus (EBV) epigenetically reprogrammes B-lymphocytes to drive immortalization and facilitate viral persistence. Host-cell transcription is perturbed principally through the actions of EBV EBNA 2, 3A, 3B and 3C, with cellular genes deregulated by specific combinations of these EBNAs through unknown mechanisms. Comparing human genome binding by these viral transcription factors, we discovered that 25% of binding sites were shared by EBNA 2 and the EBNA 3s and were located predominantly in enhancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(182 citation statements)
references
References 105 publications
(162 reference statements)
13
166
1
2
Order By: Relevance
“…In total, we identified 6,791 distinct genomic sites bound by EBNA3 proteins in LCLs. Although this estimate is comparable to that reported for EBNA3 binding in Mutu III cells (33), only 1,466 (21%) of the sites are in common (see Fig. S1 in the supplemental material).…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclssupporting
confidence: 81%
See 2 more Smart Citations
“…In total, we identified 6,791 distinct genomic sites bound by EBNA3 proteins in LCLs. Although this estimate is comparable to that reported for EBNA3 binding in Mutu III cells (33), only 1,466 (21%) of the sites are in common (see Fig. S1 in the supplemental material).…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclssupporting
confidence: 81%
“…For EBNA3B, 21% are shared with EBNA3A, 22% with EBNA3C, and 37% with EBNA2. McClellan et al found that 80% of the genes closest to an EBNA3-bound site were also the closest genes to an EBNA2-bound site (33). Using their approach, we found only 36% of EBNA3-bound genes to be EBNA2 cobound, though this proportion rises to 50% for EBNA3B-bound genes (see Table S4 in the supplemental material).…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclsmentioning
confidence: 61%
See 1 more Smart Citation
“…The best characterized of these cell proteins is RBP-J (also known as CSL), but PU.1 (7,8), ATF/CRE (9), and EBF1 binding sites (10) have also been shown to mediate EBNA-2 function at certain promoters. Early studies of EBNA-2 function fo-cused on viral promoters or artificial promoters where the binding sites are close to the transcription start site (TSS), but recent chromatin immunoprecipitation (ChIP) sequencing (ChIP-seq) studies in human B cell lines (10,11) have shown that EBNA-2 binding sites at cellular gene targets are predominantly located far away from gene TSSs, at distances up to 100 kb up-or downstream.…”
Section: Importancementioning
confidence: 99%
“…In contrast to allergic disease, it has generally been agreed that autoimmune conditions are mediated by an overactive Th1 arm of the immune system. More recently, there has been considerable debate about the role of Th2 in autoimmune conditions and the relative Th1/Th2 balance, especially in those mediated by autoantibodies such as systemic lupus erythematosis (SLE) and rheumatoid arthritis [13].…”
Section: Virusesmentioning
confidence: 99%